The Islamic secular - Jackson, Sherman A. (Oxford scholarship online, 2023)
This title argues that the meaning of 'secular' in the West and in Islam differ fundamentally. Though the Islamic secular is a 'liberation' from Islam's sacred law, shari'ah, it is neither outside 'religion' nor a rival to it; it seeks neither to discipline nor displace religion nor expand its own jurisdiction at religion's expense. The Islamic secular is, in Sherman Jackson's view, a complement to religion - in effect, a 'religious secular.' He makes the case for the Islamic secular on the basis of Islam's own pre-modern juristic tradition and shows how it impacts the relationship between Islam and the modern state, including the Islamic State.